2002
DOI: 10.1002/hbm.10074
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the hemodynamic response to auditory oddball stimuli: A six‐week test–retest study

Abstract: Determining the reliability and reproducibility of the hemodynamic response is important for the interpretation and understanding of the results of functional magnetic resonance imaging (fMRI) experiments. We describe a whole brain fMRI study designed to examine the reproducibility of the event-related hemodynamic response elicited by low-probability task-relevant target stimuli and low-probability task-irrelevant novel stimuli assessed 6 weeks apart. Reliable activation was observed during test and retest for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 57 publications
5
67
1
Order By: Relevance
“…This extensive network of brain regions associated with target detection may be similar to the attention network discussed by Mesalum (Mesulam, 1990;Mesulam, 2000). Others have suggested that processing salient stimuli is associated with an 'reflexive' or 'automatic' orienting process that is reliably activates an extensive neural network despite the low probability that all activated brain regions are required for successful task performance (Kiehl et al, 2001a;Kiehl et al, 2001b;Kiehl & Liddle, 2003;Kiehl et al, 2005).Also consistent with study hypotheses, target detection was associated with greater hemodynamic activity during the single-tone condition compared to the two-tone condition in bilateral middle temporal gyrus, inferior frontal and middle prefrontal gyri. These findings are consistent with electrophysiological and magnetoencephalogram studies of single-, two-and three-tone oddball tasks.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…This extensive network of brain regions associated with target detection may be similar to the attention network discussed by Mesalum (Mesulam, 1990;Mesulam, 2000). Others have suggested that processing salient stimuli is associated with an 'reflexive' or 'automatic' orienting process that is reliably activates an extensive neural network despite the low probability that all activated brain regions are required for successful task performance (Kiehl et al, 2001a;Kiehl et al, 2001b;Kiehl & Liddle, 2003;Kiehl et al, 2005).Also consistent with study hypotheses, target detection was associated with greater hemodynamic activity during the single-tone condition compared to the two-tone condition in bilateral middle temporal gyrus, inferior frontal and middle prefrontal gyri. These findings are consistent with electrophysiological and magnetoencephalogram studies of single-, two-and three-tone oddball tasks.…”
supporting
confidence: 72%
“…Hemodynamic activity was examined in a group of participants who performed both a two-stimulus version of the oddball and a version containing only targets (single-stimulus) (Polich et al, 1994;Polich & Heine, 1996;Polich & Margala, 1997). The first aim of this study was to determine whether the brain areas previously activated by target detection during a three-stimulus oddball task (Kiehl et al, 2001a;Kiehl et al, 2001b;Kiehl & Liddle, 2003) also were activated by the different contextual task manipulations. It was hypothesized that target stimuli would elicit hemodynamic activity in the same diverse, spatially distributed neural network implicated in previous depth electrode and three-stimulus fMRI oddball studies.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for this difference are not known, although it could be due to greater task difficulty at Time 1, although inhibition performance at the two time points was not significantly different. There are also possible effects of novelty and habituation (Fischer et al, 2003;Kiehl and Liddle, 2003;Loubinoux et al, 2001) and procedural learning (Eliassen et al, 2001) that could account for these minor differences between Time 1 and Time 2. Another possibility is that the use of four separate trial blocks at Time 1 (i.e., a longer task with more events) and a larger participant pool resulted in a higher signal to noise ratio than with two blocks at Time 2, which would have enabled better differentiation of significantly active clusters and greater inhibition-related activation compared to baseline.…”
Section: Discussionmentioning
confidence: 99%